PENGGUNAAN APLIKASI GOOGLE CLASSROOM DAN GOOGLE FORM PADA PEMBELAJARAN IPA DI MTS DARUL HIKMAH PEKANBARU - Karollina, Novi; Hidayati, Ujrah; Syaflita, Dina (PGRI Provinsi Riau, 2021)
Covid-19 is a virus that spreads very quickly. One of the government's ways to decide the spread of Covid-19 is that learning in schools is carried out online. One of the platforms that can support the implementation of online learning is the Google Classroom service. The implementation of learning cannot be separated from the assessment of learning outcomes. Assessment of learning outcomes in the Covid-19 era is also carried out online. An online application that can be used for online assessment is Google Form. MTs Darul Hikmah Pekanbaru is one of the schools that uses Google Classroom as a learning medium and Google Form as a science knowledge assessment platform as well as a means of recording student attendance. The purpose of this article research is to describe the implementation of science learning activities using Google Classroom and to describe the implementation of science knowledge assessment activities at MTs Darul Hikmah Pekanbaru during the Covid-19 pandemic. This type of research is descriptive qualitative by using data collection techniques of observation, interviews and documentation. Based on the research that has been done, it is known that the use of Google Classroom as a learning platform has been implemented well. Assessment can be easily done by teachers with Google Forms. However, there are still students who are constrained by internet access in implementing online learning. Â Â